The political economy of inequality - Stilwell, Frank J. B. (Polity Press, 2019)
"Economic inequality has become a defining issue of our age. This book, written by leading political economist Frank Stilwell, provides a comprehensive overview of the nature, causes, and consequences of the growing divide between rich and poor - and shows how there are alternative public policies that could help bridge this gap"--Provided by publisher.